2013
DOI: 10.5152/tao.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sucralfate in the Early Postoperative Improvement of Pediatric Thermal Welding Adenotonsillectomy Morbidity

Abstract: Objective: Many surgical techniques and solutions have tried to improve the morbidity of pediatric adenotonsillectomy. Pain is mainly treated with analgesics, steroids and anaesthetics. However, various topical solutions such as sucralfate have been used for pain relief. Methods: We investigated the efficacy of sucralfate together with the TW technique on post-tonsillectomy morbidity in children. Our hypothesis was that the advantages of the TW technique might be improved by the protective coating effect of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Sucralfate has been shown to have analgesic properties in various conditions. The primary action of sucralfate is idiopathic; meanwhile, several studies showed the effect of sucralfate 46,47 . Aside from the anti‐peptic effect, sucralfate increases angiogenesis and the bioavailability of growth factors, including fibroblast growth factor (FGF), epidermal growth factor (EGF), and tissue growth factor (TGF); thus, it enhances epithelialization and mucosal protection resulting in the reduction of pain and improving wound healing 36,48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sucralfate has been shown to have analgesic properties in various conditions. The primary action of sucralfate is idiopathic; meanwhile, several studies showed the effect of sucralfate 46,47 . Aside from the anti‐peptic effect, sucralfate increases angiogenesis and the bioavailability of growth factors, including fibroblast growth factor (FGF), epidermal growth factor (EGF), and tissue growth factor (TGF); thus, it enhances epithelialization and mucosal protection resulting in the reduction of pain and improving wound healing 36,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The primary action of sucralfate is idiopathic; meanwhile, several studies showed the effect of sucralfate. 46 , 47 Aside from the anti‐peptic effect, sucralfate increases angiogenesis and the bioavailability of growth factors, including fibroblast growth factor (FGF), epidermal growth factor (EGF), and tissue growth factor (TGF); thus, it enhances epithelialization and mucosal protection resulting in the reduction of pain and improving wound healing. 36 , 48 , 49 In conjunction with the pharmacodynamics of sucralfate, this study demonstrated linear results in which sucralfate is beneficial and significantly improves pain and wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation